Auctions with frictions: Recruitment, entry, and limited commitment - Stephan Lauermann; Asher Wolinsky (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Auction models are convenient abstractions of informal price-formation processes that arise in markets for assets or services. These processes involve frictions such as bidder recruitment costs for sellers, participation costs for bidders, and limitations on sellersícommitment abilities. This paper develops an auction model that captures such frictions. We derive several novel predictions; in particular, we Önd that outcomes are often ineffi cient, and the market sometimes unravels.
Keywords: D44; 330; Auctions